Overview of some knowledge about the muscle imbalance and body posture in pupils of sports hockey classes using stretching and fitball - Tothova, M. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2011)
Using compensatory training for young pupils of sport hockey classes is extremely important. It reduces the risk of muscle imbalances and poor body posture. This is demonstrated by the authors` knowledge in this report, who are dealing with the issue of locomotor's disorders. Appropriate form of release, stretching and fitness exercises can be fit ball exercises and stretching.